Conducting Polymers, Fundamentals and Applications Including Carbon Nanotubes and Graphene - Chandrasekhar, Prasanna (Springer International Publishing : Imprint: Springer, 2018)
The second edition of this popular textbook thoroughly covers the practical basics and applications of conducting polymers. It also addresses materials that have gained prominence since the first edition of this book was published, namely carbon nanotubes and graphene. The features of this new edition include: New and updated chapters on novel concepts in conducting polymers Details on interdisciplinary applications of conducting polymers An in depth description of classes of conducting polymers.